America Has Fallen: Critical Race Theory & Low-Intensity Conflict - Baker, Biff (Journal of Knowledge Management Practice, 2024)
This article aims to enlighten the business community on socio-political theory, specifically Critical Theory (CT) and Critical Race Theory (CRT), which evolved from Marxist principles. While CT focuses on economics, CRT applies a Marxist lens to race, gender, and intersectionality. The research discussion transitions from theory to application of Low Intensity Conflict (LIC) as defined by U.S. military doctrine. LIC Phase 1 involves organizing, educating, and infiltrating government; Phase 2 includes initiating low level violence and propaganda, expanding to insurrection and guerrilla attacks, and consolidating power through increased attacks and political activities. With Phases 1 and 2 completed, Phase 3 was initiated with an attempted assassination of former President Trump, and is exacerbated by unchecked immigration of military-aged men and fentanyl proliferation. This study advocates for counter-insurgency measures and emphasizes the urgent need for politicians to uphold their constitutional oaths and safeguard the nation.